PENGARUH MODEL PEMBELAJARAN READING,QUESTIONING AND ANSWERING TERHADAP KEMAMPUAN METAKOGNITIF SISWA MTS MUHAMMADIYAH 1 SAMARINDA PADA MATERI KEANEKARAGAMAN HAYATI - Fitriani, Dessy; Rambitan, Vandalita MM.; Nasution, Ruqoyyah; Herliani, Herliani; Maasawet, Elsje Theodora; Turista, Dora Dayu Rahma; Kurniawati, Zenia Lufti (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Students in grade VII at MTs Muhammadiyah 1 Samarinda have uneven metacognitive skills. This can be seen based on the inability of students to assess themselves in the teaching and learning process. The following study aims to determine “the effect of the reading, questioning and answering learning model on the metacognitive skills of MTs Muhammadiyah 1 Samarinda students” on biodiversity material. The following study applies a quantitative approach through aquasi-experiment method that applies 2 classes, with a research design of Nonequivalent control group. The sample collection was carried out through purposive sampling method, namely VII A as the experimental class and VII B as the control class. Data collection techniques and instruments are carried out through the application of tests and questionnaires. The data analysis technique uses the Independent Sample t-test test through a significance level of 0.05. The results of the test data analysistcount < ttable (0.132 < 1.683), the results of the 10 question test data analysis tcount < ttable (1.163 < 1.683) and the results of the questionnaire data analysistcount < ttable (1.543 < 1.683). So it can be concluded that there is no “effect of the reading, questioning and answering learning model on the metacognitive abilities of MTs Muhammadiyah 1 Samarinda students on biodiversity material.